Preparation for the Energy Act 2011 and minimum energy efficiency standards in UK commercial property - Mulliner, Emma; Kirsten, Louise (International Journal of Strategic Property Management, 2017)
Improving the energy performance of buildings has become a priority area for energy efficiency policy across the European Union. A cornerstone to achieving carbon reductions in UK buildings is the Energy Act 2011 and subsequent minimum energy efficiency standards. This Act contains a number of provisions which will have implications for the commercial property sector. the paper presents a quantitative study that investigates the implications of the legislation and assesses how key stakeholders, specifically commercial landlords and property agents, are preparing for its implementation. the results reveal there is generally a good awareness of the act and suggest that a number of property owners, and to a lesser extent advisers, are taking greater account of energy and environmental performance in their acquisitive due diligence and asset management strategies, as a result of the act. less preparation was evident with regard to green leasing practice, although this was being considered as an action in the near future.